Stoichiometry of C:N:P in the Roots of Alhagi sparsifolia Is More Sensitive to Soil Nutrients Than Aboveground Organs - Yin, Hui; Zheng, Hongwei; Zhang, Bo; Tariq, Akash; Lv, Guanghui; Zeng, Fanjiang; Graciano, Corina (Frontiers in Plant Science, 2021)
The stoichiometry of carbon, nitrogen, and phosphorus (C:N:P) among leaves, stems, and roots reflects trade-offs in plants for acquiring resources as well as their growth strategy. The widely distributed plant Alhagi sparsifolia is an ideal species to study the ecological stoichiometry in different organs in response to the availability of nutrients and water in the desert ecosystem. However, which organ’s response is most sensitive to environmental conditions is still unclear. To answer this question, we collected the samples of plants and soils including not only aboveground leaves and stems, but also the underground roots and soils from a wide range of arid areas during the growing season. The C, N, P, C:N, C:P, and N:P ratios in leaves, thorns, stems, and roots were derived to explore their relationship as well as their response mechanisms to nutrients and water spanning one meter deep in the soil. The results showed that the order of N concentration was leaves > thorns > stems > roots while the concentration of P inside of leaves, thorns, and stems was similar and their values were higher than that in roots. Firstly, the C:N ratios in leaves and stems were significantly positively correlated with the ratio in roots. The C:N ratios in each organ showed a significant relation with soil’s alkali hydrolysable nitrogen (SAN) above 60-cm soil depth. In addition to SAN, soil available phosphorus (SAP) and soil organic carbon (SOC) also affect the C:N ratio in roots. Secondly, the C:P and N:P ratios in aboveground organs showed no correlations with the ratios in roots. The C:P and N:P ratios in leaves and thorns have no relation with soil nutrients while the C:P ratio in roots was influenced by SAN and SOC in all soil layers. Finally, the N:P ratios in roots were also affected by nutrients in different soil depths at 0-20 cm and 60-80 cm. These results illustrated that the roots were more sensitive to soil nutrients than the aboveground parts. Our study of ecological stoichiometry also suggests a novel systematic approach for analyzing the sensitivity of organ’s response to environmental conditions.